Soil phosphorus transformation and plant uptake driven by phosphate-solubilizing microorganisms - Pang, Fei; Li, Qing; Solanki, Manoj Kumar; Wang, Zhen; Xing, Yong-Xiu; Dong, Deng-Feng (Frontiers in Microbiology, 2024)
Phosphorus (P) is an important nutrient for plants, and a lack of available P greatly limits plant growth and development. Phosphate-solubilizing microorganisms (PSMs) significantly enhance the ability of plants to absorb and utilize P, which is important for improving plant nutrient turnover and yield. This article summarizes and analyzes how PSMs promote the absorption and utilization of P nutrients by plants from four perspectives: the types and functions of PSMs, phosphate-solubilizing mechanisms, main functional genes, and the impact of complex inoculation of PSMs on plant P acquisition. This article reviews the physiological and molecular mechanisms of phosphorus solubilization and growth promotion by PSMs, with a focus on analyzing the impact of PSMs on soil microbial communities and its interaction with root exudates. In order to better understand the ability of PSMs and their role in soil P transformation and to provide prospects for research on PSMs promoting plant P absorption. PSMs mainly activate insoluble P through the secretion of organic acids, phosphatase production, and mycorrhizal symbiosis, mycorrhizal symbiosis indirectly activates P via carbon exchange. PSMs can secrete organic acids and produce phosphatase, which plays a crucial role in soil P cycling, and related genes are involved in regulating the P-solubilization ability. This article reviews the mechanisms by which microorganisms promote plant uptake of soil P, which is of great significance for a deeper understanding of PSM-mediated soil P cycling, plant P uptake and utilization, and for improving the efficiency of P utilization in agriculture.